A new undeniable signature scheme on general linear group over group ring. (4th July 2022) - Pandey, Atul; Gupta, Indivar
Abstract: The concept of undeniable signature scheme was put forward by D. Chaum and H. van Antwerpen in 1989. Such signature scheme requires the signer's co-operation at the verification step which defends the signer against the verification of his/her signature by an unwanted entity. In this paper, we propose a new undeniable signature scheme in a non-abelian group over group ring whose security relies on the difficulty of solving Factorization with Discrete Logarithm Problem (FDLP).